Warning labels and interpretive nutrition labels: Impact on substitution between sugar and artificially sweetened beverages, juice and water in a real-world selection task. (1st February 2022) - Miller, Caroline; Ettridge, Kerry; Pettigrew, Simone; Wittert, Gary; Wakefield, Melanie; Coveney, John; Roder, David; Martin, Jane; Brownbill, Aimee; Dono, Joanne
Abstract: Effective strategies to reduce free sugar intake are needed. This study examined exposure to a warning label, independently and in conjunction with a Health Star Rating (HSR) label, on the selection of commercially available cold beverages with real decision-making stakes. Participants (N = 511, 47.9% female, mean = 21.7 (SD = 6.1) years) accessed an online convenience store app via an on-campus laptop to select one of 10 beverages (5 sugar-sweetened beverages [SSBs], 1100% fruit juice, 2 artificially sweetened beverages [ASBs] and 2 waters). The task was repeated with the addition of a warning label on high-sugar drinks in Round 2, and the addition of an HSR label on all drinks in Round 3. Participants were informed that they would receive a complementary drink (valued at <5AUD) based on their selections following the completion of a brief questionnaire. Baseline results indicated that SSBs and waters were the most and least popular choices, respectively. For both males and females, there was a significant decrease in SSB selection (p < 0.001) and significant increase in ASB and water selection (p < 0.001) following the addition of warning labels to high-sugar drinks. The decreased selection of SSBs and increased selection of waters was maintained in Round 3 when HSR labels were added to all drinks. 100% fruit juice selection decreased with the addition of a warning label for females only (p < 0.01), but increased following the addition of a 4-star HSR label, for both males (p < 0.05) and females (p < 0.001). Warning labels reduced young adults' selection of SSBs and promoted substitution to water. The HSR reinforced this effect for the least healthy drinks. Increased water selection may be further enhanced by ensuring that warning label thresholds and HSR algorithms align to present consistent messaging.